A Flutter-Based Mobile Inventory Management System for Improving Stock Control in Furniture and Electronic Businesses - Ahmad Khaerudin; Basuki Rakhim Setya Permana; Sigit Auliana; Gagah Dwiki Putra Aryono (ARRUS Journal of Engineering and Technology, 2026)
Inventory management plays a critical role in maintaining the efficiency of business operational activities. However, many small and medium-sized enterprises still rely on manual inventory recording systems, resulting in data inaccuracies, reporting delays, and difficulties in monitoring stock availability. This study aims to develop and implement a mobile-based inventory management information system using the Flutter framework integrated with Firebase database technology. The research was conducted at PT Mandiri Jaya, a company specializing in furniture and electronic product sales in Pandeglang Regency, Indonesia. The proposed system was designed to support real-time stock-in and stock-out transaction recording, product data management, and automated inventory reporting. This study employed a system development methodology consisting of requirement analysis, system design, application development, implementation, and system testing. The results indicate that the developed application successfully improves the efficiency and accuracy of inventory management processes, minimizes human errors in data recording, and provides faster access to inventory information for managerial decision-making. Furthermore, the implementation of Flutter technology enables cross-platform mobile access and enhances the overall effectiveness of inventory management operations.